2014
DOI: 10.1111/plb.12265
|View full text |Cite
|
Sign up to set email alerts
|

Variation in plant‐mediated interactions between rhizobacteria and caterpillars: potential role of soil composition

Abstract: Selected strains of non-pathogenic rhizobacteria can trigger induced systemic resistance (ISR) in plants against aboveground insect herbivores. However, the underlying mechanisms of plant-mediated interactions between rhizobacteria and herbivorous insects are still poorly understood. Using Arabidopsis thaliana Col-0-Pseudomonas fluorescens WCS417r as a model system, we investigated the performance and the molecular mechanisms underlying plant-mediated effects of rhizobacteria on the generalist caterpillar Mame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 52 publications
1
74
2
Order By: Relevance
“…WCS417r was quantified in wild type plants and mutants to confirm that the colonization met the required threshold for ISR of 10 5 cfu.g −1 root (Raaijmakers et al 1995). The rhizobacteria quantification was done following the method described in Pangesti et al (2015), with slight modification. Roots were harvested, weighed, and shaken vigorously for 1 min in 10 ml of 10 mM MgSO 4 containing 0.5 g of glass beads (425–600 μm, Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…WCS417r was quantified in wild type plants and mutants to confirm that the colonization met the required threshold for ISR of 10 5 cfu.g −1 root (Raaijmakers et al 1995). The rhizobacteria quantification was done following the method described in Pangesti et al (2015), with slight modification. Roots were harvested, weighed, and shaken vigorously for 1 min in 10 ml of 10 mM MgSO 4 containing 0.5 g of glass beads (425–600 μm, Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have found that this rhizobacterium triggers an enhanced expression of the JA-regulated gene LOX2 and the JA/ET-regulated genes PDF1.2 and HEL upon feeding by the generalist caterpillars M. brassicae and Spodoptera exigua (Pangesti et al 2015; Van Oosten et al 2008). However, whether the JA-regulated MYC2-branch or the JA/ET-regulated ORA59-branch is modulating plant defense in rhizobacteria-mediated ISR against insects is unknown.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Mamestra brassicae eggs were obtained from the laboratory of Entomology at Wageningen University where they were reared as described previously (Pangesti et al, 2015). Per 5-week-old Arabidopsis plant, one freshly hatched first-instar (L1) larva was directly placed on a leaf using a fine paintbrush.…”
Section: Insect Performance and Disease Bioassaysmentioning
confidence: 99%
“…Subsequently cDNA was diluted by a factor of 1:20 with RNase free water. For RT-qPCR analysis specific primers were used for 5 genes involved in the 3 main plant defence pathways regulated by ET, JA or SA respectively: VSP2 (At5g24770; JA-dependent) (Anderson et al 2004), PDF1.2 (At5g44420; JA-and ET-dependent), PR1 (At2g14610; SAdependent) , HEL (At3g04720; ET-dependent) (Pangesti et al 2015) and CYP79B3, involved in glucosinolate synthesis and inducible by jasmonic acid treatment (At2g22330; JA-dependent) (Lemarié et al 2015) (for all primer sequences see Supplementary Information Table S2). In addition, the expression of the reference genes FBOX (At5g15710) (Remans et al 2008) and GAPDH (At3g04120) ) was assessed for normalization.…”
Section: Rna Extraction and Quantitative Rt-pcr Analysismentioning
confidence: 99%